Winners and losers on the roller-coaster: Ireland, 2003 - 2011 - David Madden (University College Dublin, UCD School of Economics, 2013)
This paper applies the methodology of Ravallion and Chen in calculating growth incidence curves for Ireland over the 2003-2011 period, using measures of equivalised disposable income from the Survey of Income and Living Conditions (SILC). These curves provide an indication of growth at different percentiles of the distribution and may be used to address the issue of whether growth was pro-poor or not. The analysis suggests that growth was broadly pro-poor over the period as a whole and also over two sub-periods of 2003-2007 and 2008-2011, reflecting periods of boom and recession respectively. However, the results must be qualified by the fact that the income measure may not completely capture living standards as it deals incompletely with housing costs and state provided services.
Keywords: I31; I32; O4; 330; pro-poor growth; poverty efficient growth rate